Cost variation analysis of commonly prescribed anti-diabetic drugs available in Indian market: a pharmaco-economic study - Gupta, Kajal S.; Pardeshi, Milind L.; Hiray, Rajesh S. (International Journal of Basic & Clinical Pharmacology, 2021)
Background: Diabetes mellitus (DM) is a chronic metabolic disorder requiring lifelong treatment. Due to rapid expansion of urbanization, unhealthy diet habits and sedentary lifestyle, the incidence of DM is increasing. The chronic nature of DM causes significant personal suffering and economic difficulty to families. The was aimed at investigating the cost difference in various brands of the same oral anti-diabetic drug. Methods: The minimum and the maximum cost in rupees (INR) of a particular anti-diabetic drug manufactured by various pharmaceutical companies were obtained from current index of medical specialties (CIMS) website, Indian drug review (IDR) 2021 issue and National pharmaceutical pricing authority-pharma sahi daam. The cost ratio and percentage cost variation were noted for each brand. Results: Amongst single drug therapy, metformin 500 mg sustained release showed highest price variation (3668%). Minimum cost variation was found with glipizide 2.5 mg (65%). Amongst the fixed dose combinations, highest cost variation was seen with glimepiride 2 mg+metformin 1000 mg (2703%) while minimum cost variation was found with repaglinide 1 mg+voglibose 0.3 mg (29%). Conclusions: A noticeable cost variation was found in different brands of the same anti-diabetic drug. Prescribing a more expensive brand when a cheaper one is available can burden the patient financially and thus reduce patient compliance. In addition, the Government should also include more anti-diabetic drugs under the price control policy to ensure that affordable and efficacious medicines are available to all. Background: Diabetes mellitus (DM) is a chronic metabolic disorder requiring lifelong treatment. Due to rapid expansion of urbanization, unhealthy diet habits and sedentary life style, the incidence of DM is increasing .The chronic nature of DM causes significant personal suffering and economic difficulty to families. The present study aims at investigating the cost difference in various brands of the same oral anti-diabetic drug. Methods: The minimum and the maximum cost in rupees (INR) of a particular anti-diabetic drug manufactured by various brands were obtained from Current Index of Medical Specialties (CIMS) website, Indian Drug Review (IDR) 2021 issue and National Pharmaceutical Pricing Authority – Pharma sahi daam. The cost ratio and percentage cost variation were noted for each brand. Results: Amongst single drug therapy, Metformin 500mg Sustained Release showed highest price variation (3668%). Minimum cost variation was found with Glipizide 2.5mg (65%). Amongst the fixed dose combinations, highest cost variation was seen with Glimepiride 2mg + Metformin 1000mg (2703%) while minimum cost variation was found with Repaglinide 1mg + Voglibose 0.3mg (29%). Conclusions: A noticeable cost variation was found in different brands of the same anti-diabetic drug. Prescribing a more expensive brand when a cheaper one is available can burden the patient financially and thus reduce patient compliance. In addition, the Government should also include more anti-diabetic drugs under the price control policy to ensure that affordable and efficacious medicines are available to all. Keywords: Anti-diabetic agents, Cost variation, Pharmaco-economics, Adherence, Brands Background: Diabetes mellitus (DM) is a chronic metabolic disorder requiring lifelong treatment. Due to rapid expansion of urbanization, unhealthy diet habits and sedentary life style, the incidence of DM is increasing .The chronic nature of DM causes significant personal suffering and economic difficulty to families. The present study aims at investigating the cost difference in various brands of the same oral anti-diabetic drug. Methods: The minimum and the maximum cost in rupees (INR) of a particular anti-diabetic drug manufactured by various brands were obtained from Current Index of Medical Specialties (CIMS) website, Indian Drug Review (IDR) 2021 issue and National Pharmaceutical Pricing Authority – Pharma sahi daam. The cost ratio and percentage cost variation were noted for each brand. Results: Amongst single drug therapy, Metformin 500mg Sustained Release showed highest price variation (3668%). Minimum cost variation was found with Glipizide 2.5mg (65%). Amongst the fixed dose combinations, highest cost variation was seen with Glimepiride 2mg + Metformin 1000mg (2703%) while minimum cost variation was found with Repaglinide 1mg + Voglibose 0.3mg (29%). Conclusions: A noticeable cost variation was found in different brands of the same anti-diabetic drug. Prescribing a more expensive brand when a cheaper one is available can burden the patient financially and thus reduce patient compliance. In addition, the Government should also include more anti-diabetic drugs under the price control policy to ensure that affordable and efficacious medicines are available to all. Keywords: Anti-diabetic agents, Cost variation, Pharmaco-economics, Adherence, Brands Background: Diabetes mellitus (DM) is a chronic metabolic disorder requiring lifelong treatment. Due to rapid expansion of urbanization, unhealthy diet habits and sedentary life style, the incidence of DM is increasing .The chronic nature of DM causes significant personal suffering and economic difficulty to families. The present study aims at investigating the cost difference in various brands of the same oral anti-diabetic drug. Methods: The minimum and the maximum cost in rupees (INR) of a particular anti-diabetic drug manufactured by various brands were obtained from Current Index of Medical Specialties (CIMS) website, Indian Drug Review (IDR) 2021 issue and National Pharmaceutical Pricing Authority – Pharma sahi daam. The cost ratio and percentage cost variation were noted for each brand. Results: Amongst single drug therapy, Metformin 500mg Sustained Release showed highest price variation (3668%). Minimum cost variation was found with Glipizide 2.5mg (65%). Amongst the fixed dose combinations, highest cost variation was seen with Glimepiride 2mg + Metformin 1000mg (2703%) while minimum cost variation was found with Repaglinide 1mg + Voglibose 0.3mg (29%). Conclusions: A noticeable cost variation was found in different brands of the same anti-diabetic drug. Prescribing a more expensive brand when a cheaper one is available can burden the patient financially and thus reduce patient compliance. In addition, the Government should also include more anti-diabetic drugs under the price control policy to ensure that affordable and efficacious medicines are available to all. Keywords: Anti-diabetic agents, Cost variation, Pharmaco-economics, Adherence, Brands